The potential impact of GLS and PDHA1 on tumor immunity and immunotherapy response in LUSC - Ling, Tianhe; Wu, Jiahui; Xiaohao, Ling (Frontiers in Genetics, 2025)
BackgroundLung squamous cell carcinoma (LUSC), a therapeutically challenging non-small cell lung cancer (NSCLC) subtype with a poor prognosis, exhibits heterogeneous responses to immunotherapy. Cuproptosis, a recently discovered regulated cell death pathway, has been hypothesised to modulate the tumour immune microenvironment (TIME). Despite the well-established role of PDHA1 as a metabolic regulator, the specific mechanisms by which it interacts with GLS in cuproptosis-mediated immune-metabolic crosstalk remain to be elucidated in LUSC. The present study investigates the manner in which GLS/PDHA1 expression patterns influence TIME composition and contribute to the stratification of immunotherapy responsiveness.MethodsIt was determined that GLS and PDHA1 were the most significant copper oxidation-related genes, due to their highest absolute correlation with the ESTIMATE immune score. A consensus clustering analysis was conducted on a cohort of 501 TCGA-LUSC patients, with the objective of stratifying patients based on GLS/PDHA1 expression levels. Quantitative analysis of immune infiltration was performed using ESTIMATE, CIBERSORT, and ssGSEA methods. The pathway enrichment analysis was conducted using GSEA and WGCNA. A detailed analysis of 17,050 single-cell RNA sequencing (scRNA-seq) data from two LUSC patients was conducted, which revealed unique gene expression patterns. The validity of these findings was confirmed through the integration of four independent GEO cohorts (GSE181043/37745/43580/115457; n = 278).ResultsConsensus clustering delineated two subtypes:Cluster 1 (low GLS/high PDHA1) and Cluster 2 (high GLS/low PDHA1). Cluster two showed enhanced immune infiltration, characterized by: Elevated immune checkpoint expression and Enriched T-cell activation pathways. Validation across four GEO cohorts confirmed Cluster two conserved immune-hot phenotypewith elevated ESTIMATE stromal scores, reduced tumor purity, and activated immune subsets. scRNA-seq identified malignant epithelial cells as the hub of divergent GLS/PDHA1 expression (high GLS/low PDHA1), orchestrating cuproptosis-immunometabolic crosstalk.ConclusionGLS and PDHA1 have been proposed as potential prognostic markers for immunotherapy. Targeting cuproptosis has the potential to convert immunologically cold to hot tumours, thereby advancing precision immunotherapy.